2012
DOI: 10.1007/s00296-012-2537-7
|View full text |Cite
|
Sign up to set email alerts
|

The predictive factors of low serum 25-hydroxyvitamin D and vitamin D deficiency in patients with systemic lupus erythematosus

Abstract: Vitamin D is a steroid hormone with pleiotropic effects. The association between serum 25-hydroxyvitamin D level [25(OH) D] and lupus nephritis are not clearly known. We aim to determine serum 25(OH) D levels in patients with inactive SLE, active SLE without lupus nephritis (LN) and active SLE with LN and to identify clinical predictor of vitamin D deficiency. One hundred and eight SLE patients were included. Patients were classified as Group (Gr) 1, 2 and 3 if they had SLE disease activity index (SLEDAI) <3, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
52
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(57 citation statements)
references
References 27 publications
3
52
0
Order By: Relevance
“…SLE also affects other organ systems, including the kidneys, where 25[OH]D is converted to its metabolically active form 1,25[OH] 2 D, possibly leading to decreased levels of vitamin D in these individuals. 64 Only one individual had medical record confirmed renal criteria at baseline, however, indicating that this is likely not an issue within this cohort.…”
Section: [Oh]mentioning
confidence: 84%
“…SLE also affects other organ systems, including the kidneys, where 25[OH]D is converted to its metabolically active form 1,25[OH] 2 D, possibly leading to decreased levels of vitamin D in these individuals. 64 Only one individual had medical record confirmed renal criteria at baseline, however, indicating that this is likely not an issue within this cohort.…”
Section: [Oh]mentioning
confidence: 84%
“…Previous studies have shown the high prevalence of vitamin D deficiency in adults and adolescents with SLE [21,[27][28][29][30][31][32][33]. The use of corticosteroids, recommendations to avoid sun exposure, and kidney impairment are risk factors for this deficiency [21].…”
Section: Discussionmentioning
confidence: 97%
“…The effect of drugs such as glucocorticoids, calcineurin inhibitors, and anticonvulsants, as well as compromised 1α-hydroxylation of 25-(OH)D 3 due to renal insufficiency, further contribute to low vitamin D in patients with SLE [71,72,73]. …”
Section: Hypovitaminosis D and Its Impact On Disease Activity And mentioning
confidence: 99%